Effect of human placental extract in the management of biofilm mediated drug resistance – A focus on wound management. (October 2017) - Goswami, Sutapa; Sarkar, Ratul; Saha, Pritam; Maity, Amit; Sarkar, Tridib; Das, Debmalya; Chakraborty, Piyali Datta; Bandyopadhyay, Subhasri; Ghosh, Chandan Kumar; Karmakar, Sanmoy; Sen, Tuhinadri
Abstract: Management of infectious wounds, particularly chronic wounds and burn injuries, is a matter of global concern. Worldwide estimates reveal that, billions of dollars are being spent annually for the management of such chronic ailments. Evidently, bacterial biofilms pose a greater problem in the effective management of infection in chronic wounds, since most of the currently available antibiotics are unable to act on the microorganisms residing inside the protected environment of the biofilms. Accordingly, in the present study, we have attempted to evaluate the anti-biofilm properties of human placental extract (PLX) and also other virulence factors that are mediated via the quorum sensing (QS) signalling system. PLX is well known for its anti inflammatory action and it has been shown earlier some anti microbial and enzymatic activity also. PLX was found to produce significant inhibition of biofilm formation and also decreased the levels of pyoverdin and pyocyanin. The microscopic analysis (both light microscopy and atomic force microscopy) of biofilms was also used for substantiating the findings from spectrophotometric (crystal violet estimation) and fluorescence analysis (resazurin uptake). PLX pre-treatment decreased the hydrophobicity of gram-positive and gram negative cells, indicating the effect of placental extract on adherence property of planktonic cell, serving as an indicator for its antibiofilm effect on microorganisms. The reduced extracellular DNA (eDNA) content in biofilm matrix following treatment with PLX also indicates the effectiveness of placenta extract on bacterial adherence, which in turn serves as evidence substantiating the antibiofilm effects of the PLX. Furthermore, PLX was also found to be significantly effective in the in vitro wound biofilm model. Thus the present study, the first of its kind with PLX, establishes the therapeutic benefit of the same particularly in infected wounds, opening up newer avenue for further exploration.